IMPLEMENTASI MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN PEMAHAMAN KONSEP JENIS MATA PENCAHARIAN DI LINGKUNGAN SEKITAR BAGI SISWA SEKOLAH DASAR - Amira Henny Mahmudah; Imaniar purbasari; Ika Ari Pratiwi; Erik Aditia Ismaya (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The objectives of this study were 1) to analyze the improvement of teacher teaching skills in improving students 'conceptual understanding using the picture and picture model of learning on the material types of livelihoods in the surrounding environment 2) to analyze the improvement of students' conceptual understanding using the picture and picture model on the type of livelihood in surrounding environment.The research method used is classroom action research. This research was conducted in two cycles, each of which consisted of planning, acting, observing, and reflecting. The research subjects were the fourth grade students of SD 2 Jojo Kudus with a total of 20 students. The data sources of this research are teachers, students. Data collection techniques include observation techniques, and tests. The data analysis used was qualitative and quantitative data analysis. Quantitative data analysis was used to calculate the increase in students' conceptual understanding using the picture and picture model.The results showed that an increase in teacher teaching skills occurred in every indicator between cycle I to cycle II. The teaching skills of teachers in cycle II have increased and in general the teachers have implemented the steps of the picture and picture learning model properly. The application of the picture and picture model can also improve students' conceptual understanding skills at SD 2 Jojo Kudus in understanding types of livelihoods. The students' understanding of the concept of social studies content in the first cycle obtained a success percentage of 75% with very good criteria, then the second cycle obtained a percentage of 94% with very good criteria